Optimizing Corporate Communication Paradigms A Five-Dimensional Framework For Digital Dialogic Engagement Via Social Networks - Salman Alam (Integrative Perspectives of Social and Science Journal, 2026)
Digital evolution and the proliferation of social networking platforms have fundamentally reshaped modern public relations, fostering a shift toward balanced, two-way digital communication. Contemporary entities progressively leverage diverse social media architectures to amplify brand prominence and cultivate strategic stakeholder relations. These digital avenues facilitate seamless information dissemination, proactive listening, and meaningful online interaction with diverse publics. Given that social networks now function as a cornerstone of corporate communication strategy, this paper provides an analytical evaluation of digital dialogic interactions. It introduces a novel conceptual model structured around five core pillars: continuous operational presence, collaborative attitude, interactive asset deployment, real-time responsiveness, and strategic online conversation. By dissecting these dimensions, the study elucidates their distinct impacts on cultivating public engagement. Ultimately, these insights offer valuable strategic implications for communication executives and organizational theorists, while charting prospective directions for future scholarly inquiry.